The Effectiveness of Tai Chi Exercise in Reducing Depression Levels in Adults - Varentina Lailatul Nisa Maharani; Wachidah Yuniartika (Indonesian Journal of Global Health Research, 2026)
Depression is a mental health disorder that is more commonly experienced in adulthood. At this stage, individuals begin to experience various changes, both physically and in terms of their social roles, interpersonal relationships, and lifestyle patterns. These changes can affect emotional balance and increase the risk of depression. One non-pharmacological intervention that can help overcome depression is Tai Chi. This study aims to analyze the effectiveness of Tai Chi on depression levels in adults in the community. This study used a quantitative approach with a quasi-experimental design in the form of a one-group pretest-posttest design without a control. The sample consisted of 30 respondents selected using accidental sampling and meeting the inclusion criteria of being aged 18–59 years with mild to moderate depression. The instrument used was the PHQ-9 questionnaire with a validity score of 0.508–0.907. The intervention consisted of Tai Chi exercises comprising eight movements, performed three times a week for 30 minutes independently at home. The data were analyzed using the Wilcoxon test to see if there was a difference in depression levels before and after the intervention. Before the intervention, the majority of respondents experienced mild depression, while after the intervention, the majority of respondents showed no symptoms of depression. The Wilcoxon test showed a Z value of -4.899 with p = 0.001. Tai Chi exercises have a significant effect in reducing depression levels in adults in the community. Tai Chi exercises can be used as an alternative non-pharmacological intervention to improve the mental health of adults in the community.